Sociolinguistic Study of Asep Balon's Lexical Song Lyrics and its Relevance to Netizens' Character Education - Sri Rahayu; Syihabbudin Syihabbudin; Asep Hikmat (Universitas Stikubank (UNISBANK) Semarang, 2023)
Sundanese is one of the largest regional languages in Indonesia, which has correlation to the character of speakers with the presence of undak usuk basa. This study analyzes the lyrics of a Sundanese song entitled Hakan Tah Ku Sia. From the title, it can be seen that there is something odd in the choice of language that is suitable for use among the general public, especially in the form of songs that will surely spread without limit, especially among the Sundanese. The purpose of this study is to describe the characteristics of the language used in the song lyrics of Hakan Tah Ku Sia, by Asep Balon, a young rapper from Bandung, to identify the themes and goals that the song lyricists want to convey, and to describe the functions that lie behind the variations in themes and variations in the purpose of creating song lyrics. Hakan Tah Ku Sia by Asep Balon, based on an analysis of social factors in the environment of singers and consumers. The data sources are the lyrics of the song Hakan Tah Ku sia, and Tik Tok and YouTube netizens' comments on the song. language rules because of the creator's desire to gain freedom of expression, poetic effects, beauty, tones of harmony between lyrics and melody, which make it easier for the audience to hear and enjoy the song. The creation of the lyrics of the song Hakan Tah Ku Sia. From the analysis involving social factors contained in the speech component, it was found that the function of song lyrics in society also varies